Single-Cell Ribonucleic Acid Sequencing Clarifies Cold Tolerance Mechanisms in the Pacific White Shrimp (Litopenaeus Vannamei) - Zhu, Weilin; Yang, Chunling; Chen, Xiuli; Liu, Qingyun; Li, Qiangyong; Peng, Min; Wang, Huanling; Chen, Xiaohan; Yang, Qiong; Liao, Zhenping; Li, Min; Pan, Chuanyan; et al. (Frontiers in Genetics, 2022)
To characterize the cold tolerance mechanism of the Pacific white shrimp (Litopenaeus vannamei), we performed single-cell RNA sequencing (scRNA-seq) of ~5185 hepatopancreas cells from cold-tolerant (Lv-T) and common (Lv-C) L. vannamei at preferred and low temperatures (28°C and 10°C, respectively). The cells fell into 10 clusters and 4 cell types: embryonic, resorptive, blister-like, and fibrillar. We identified differentially expressed genes between Lv-T and Lv-C, which were mainly associated with the terms "immune system," "cytoskeleton," "antioxidant system," "digestive enzyme," and "detoxification," as well as the pathways "metabolic pathways of oxidative phosphorylation," "metabolism of xenobiotics by cytochrome P450," "chemical carcinogenesis," "drug metabolism-cytochrome P450," and "fatty acid metabolism." Reconstruction of fibrillar cell trajectories showed that, under low temperature stress, hepatopancreas cells had two distinct fates, cell fate 1 and cell fate 2. Cell fate 1 was mainly involved in signal transduction and sensory organ development. Cell fate 2 was mainly involved in metabolic processes. This study preliminarily clarifies the molecular mechanisms underlying cold tolerance in L. vannamei, which will be useful for the breeding of shrimp with greater cold tolerance.